Initial clinical experience with Ahmed Valve implantation in refractory pediatric glaucoma - Katia Novak-Lauš; Jelena Škunca Herman; Marija Šimić Prskalo; Darija Jurišić; Zdravko Mandić (Acta Clinica Croatica, 2016)
The purpose is to report on the safety and efficacy of Ahmed Glaucoma Valve (AGV, New World Medical, Inc., Rancho Cucamonga, CA, USA) implantation for the management of refractory pediatric glaucoma observed during one-year follow up period. A retrospective chart review was conducted on 10 eyes, all younger than 11 years, with pediatric glaucoma that underwent AGV implantation for medicamentously uncontrolled intraocular pressure (IOP) between 2010 and 2014. Outcome measures were control of IOP below 23 mm Hg (with or without antiglaucoma medications) and changes in visual acuity. Complications were recorded. After AGV implantation, IOP values ranged from 18 mm Hg to 23 mm Hg (except for one eye with postoperative hypotonia due to suprachoroid hemorrhage, where the postoperative IOP value was 4 mm Hg). The number of antiglaucoma medications was reduced, i.e. four patients had two medications, one patient had one medication, and the others did not need antiglaucoma medication on the last follow-up visit. One eye had suprachoroid hemorrhage, one eye had long-term persistent uveitic membrane, and two eyes had tube-cornea touch. In conclusion, AGV implantation appears to be a viable option for the management of refractory pediatric glaucoma and shows success in IOP control. However, there was a relatively high complication rate limiting the overall success rate.